Power generation with negative CO2 emissions through bio-electricity with CCS using dry co-gasification of coal-biomass blends - Vasireddy, Satyam Naidu; Jayanti, Sreenivas (Clean Technologies and Environmental Policy, 2024)
Among the measures proposed for decarbonization of electricity generation, large reductions in CO2 emissions are possible by the adoption of bio-electricity with carbon dioxide capture and sequestration. In the present study, thermodynamic analysis of a thermal power plant that produces electricity through co-gasification of high-ash coal and Casuarina equisetifola (CE), a crop which grows along the Indian coastline, and which is not in competition with other agricultural crops for land and water use, is considered for integrated gasification combined cycle (IGCC) with CO2 capture via oxyfuel combustion and gasification technology. The integrated power plant layout includes the energy required for CO2 gasification of coal, biomass blended fuel, air separation to produce oxygen for oxyfuel combustion as well as for purification and compression of the flue gas up to 30 bar. Simulation results show that a net efficiency of 37% can be achieved using high-ash Indian coal and CE blends up to 30% of the latter. Synergetic effect of co-gasification components is observed in mass, molar and thermal energy flowrates for biomass blended fuel. With the help of CCS, CO2 emissions are reduced to 69.91 gCO(2)/kWh for 100% coal-based IGCC-CC plant and further to -21.69 gCO(2)/kWh (negative CO2 emissions) for 30% biomass blending, thus paving way for CO2-negative power generation.
Keywords: BECCS; Combustion; Dry co-gasification; IGCC-CC plant; Negative CO2 emissions; Oxyfuel; Thermodynamic analysis